(untitled) (Revista Electrónica REDINE, 2018)
One of the policies of the University Centroccidental Lisandro Alvarado (UCLA) is the allocation of changes that allow academic integration for the production of research that promote sustainable development, the training of integral professionals and the exchange of knowledge, according to the requirements of the society. In order to determine the scope of the Deanship of Veterinary Sciences (DCV) in compliance with this institutional policy, we set ourselves the objective of evaluating the relationship of the CSD with the agricultural sector of the Central-Western region. This descriptive, observational, follow-up, and retrospective research was based on published documents from the DCV Research Coordination over the last five (5) years as well as the Functional Research Units. Dr. Haity Moussatché "(UNIHM) and the Veterinary Parasitology Unit (UNIPARVET) Criteria for evaluation: research projects, publications, knowledge dissemination, advice and services, framed in the lines of research that have an impact on the agricultural sector The evaluation and communication of how the link has been made in these five years, as well as the learning and technological assimilation of undergraduate and graduate students, researchers and the producers themselves, is a way to show the presence of the University in the scientific, technological, innovative and productive development of the region and the country.